Engineering education - the hidden agenda - Abdul Mukti, Mohamad Afifi; Mohd. Noor, Fatimah (2004)
The demand for engineering education is growing rapidly especially in a developing country, such as ours. The engineering profession is still a respectable profession. The growth in engineering education covers both the physical count and the varieties of specialisations and fields of engineering. Taking advantage of this situation, institutions of higher learning are marketing engineering programmes to look as if they are highly sought-after commodities. In pursuing their ambitious strategies to promote programmes, these institutions have to adapt to the market needs and implement several changes and modifications, such as, on entry qualifications, academic systems and modes of instruction, just to mention a few. Although providing new opportunities to the public, these modifications may affect, on the other hand, quality, effectiveness and integrity of the programme, thus the profession. Some of the education providers that offer engineering programmes are just giving degrees, but not education. On paper, depending on the type of institution, these programmes seem to meet the requirements of either EAC or LAN. However, under closer scrutiny, there are too many weaknesses and loopholes especially at the implementation stage. This paper highlights the problems and possible consequences on the current practice of the institutions of higher learning in imparting their engineering programmes. It relates to personal experience and findings from accreditation process done for LAN and EAC on some engineering programmes of public and private institutions of higher learning. The issues mentioned here may provide a kind of framework within which it can be developed to control the quality of engineering education in Malaysia.